2015
DOI: 10.1111/rode.12133
|View full text |Cite
|
Sign up to set email alerts
|

Financial Deepening and Economic Growth in Advanced and Emerging Economies

Abstract: While over‐financing caused crises and slow growth in advanced economies including Germany, France and the UK after 2008, more prudent financial deepening sustained higher economic growth in China and India—two major emerging economies in the world. The actual financial deepening ratios (AFDR) observed in the non‐consolidated balance sheet from the OECD exceeded by factors of 3.5, 2.4 and 5.1 the optimal financial deepening ratios (OFDR) obtained from the solutions of dynamic general equilibrium (DGE) models o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…To test the robustness of the results, in Table 2, neither of the columns (1) and (3) includes other control variables but the annual dummy variables, while both of the columns (2) and (4) include all the control variables. For population ageing, both coefficients on the indicator ln(COA) in columns (1) and (2) as well as both coefficients on the indicator ln(OAD) in columns (3) and (4) are significantly positive at the 1% confidence level. It suggests that since entering an ageing society in 2000, population ageing has boosted China's economic growth.…”
Section: Empirical Methodologymentioning
confidence: 88%
See 1 more Smart Citation
“…To test the robustness of the results, in Table 2, neither of the columns (1) and (3) includes other control variables but the annual dummy variables, while both of the columns (2) and (4) include all the control variables. For population ageing, both coefficients on the indicator ln(COA) in columns (1) and (2) as well as both coefficients on the indicator ln(OAD) in columns (3) and (4) are significantly positive at the 1% confidence level. It suggests that since entering an ageing society in 2000, population ageing has boosted China's economic growth.…”
Section: Empirical Methodologymentioning
confidence: 88%
“…With rapid economic growth that even surpassed most developed countries and increasing international influence over the past two decades in China, the factors that affect China's economic growth have attracted much attention. Population ageing and financial deepening are two important factors affecting economic growth in developed countries [1,2]. Evidence from developed countries showed that the process of population ageing and financial deepening reform took place in different periods.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of addition Hansen (2014), Fama (2014), Shiller (2014), and Weale (2014) provide theoretical insights in the development of Chinese economy. On the empirical aspect Bhattarai (2015) explains the dynamic CGE model of China for analysis of financial deepening issues. Zhou (2014), Luo and Ying (2014), Zhu, Whalley, and Zhao (2014), Fu, Abrokwa, and Bhattarai (2014), Hsua, Tian, and Xua (2014), Liu and Hsu (2014) review issues relating to the role of public and private sectors in the Chinese economy.…”
Section: Literature On the Chinese Economymentioning
confidence: 99%
“…It confirms financial deepening as the candidate for the threshold effect in the finance-growth relationship. Excess financial depth has severally been reported as the source of reversal in growth after a given threshold value inCole (1974);Darrat (1999);Rousseau and Wachtel (2011);Cecchetti and Kharroubi (2012); andBhattarai (2015).…”
mentioning
confidence: 99%